Being Church with the Kawasi Community: A Church Advocacy Theology on the Impact of Nickel Mining by PT. Harita Group in Kawasi Village – Obi Island - Lakoruhut, Esrom; Batlajery, Agustinus Martin Luther; Iwamony, Rachel (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2025)
This article aims to describe the role of the church in addressing the socio-economic injustice caused by the Nickel mining company in Kawasi village. In this writing, the author uses a qualitative method, relying on reliable library sources such as books, articles, and journals. In addition, the author conducted field research in Kawasi village by interviewing several community members to collect data for this writing. The presence of PT. Harita Group, one of the nickel mining companies that exploits Kawasi village, has a destructive impact on the Kawasi community. The destructive impact in question is the loss of community subsistence, namely, living spaces, health problems, clean water crises, and disturbances to security, order, and cultural degradation. In the reality experienced by the Kawasi community, the church is required to understand its calling and role and advocate for the Kawasi community, as well as to the government and companies.